Kidney Organoids Generated Using an Allelic Series of NPHS2 Point Variants Reveal Distinct Intracellular Podocin Mistrafficking. Issue 1 (27th January 2023) - Dorison, Aude; Ghobrial, Irene; Graham, Alison; Peiris, Thanushi; Forbes, Thomas A.; See, Michael; Das, Mithun; Saleem, Moin A.; Quinlan, Catherine; Lawlor, Kynan T.; Ramialison, Mirana; Howden, Sara E.; et al.
Abstract : Significance Statement: Missense variants of NPHS2 that cause mistrafficking of the encoded protein, PODOCIN, have been associated with steroid-resistant nephrotic syndrome. However, most studies have overexpressed such variants in 2D nonpodocyte cells. This study describes the generation and characterization of human kidney organoids representing an allelic series of homozygous NPHS2 missense variants. The strategy revealed a previously unappreciated reduction in variant PODOCIN protein, variant-specific subcellular localization, and specific effects on NEPHRIN association. All variants showed apoptosis in the absence of endoplasmic reticulum stress. Engineering endogenous NPHS2 variants to model in 3D human organoids provides a more accurate view of the pathobiology and a toolkit to screen compounds for reduction of variant protein degradation and mistrafficking. Abstract : Background: NPHS2 variants are the most common cause of steroid-resistant nephrotic syndrome in children >1 month old. Missense NPHS2 variants were reported to cause mistrafficking of the encoded protein, PODOCIN, but this conclusion was on the basis of overexpression in some nonpodocyte cell lines. Methods: We generated a series of human induced pluripotent stem cell (iPSC) lines bearing pathogenic missense variants of NPHS2, encoding the protein changes p.G92C, p.P118L, p.R138Q, p.R168H, and p.R291W, and control lines. iPSC lines were also generated from a patient with steroid-resistant nephrotic syndrome (p.R168H homozygote) and a healthy heterozygous parent. All lines were differentiated into kidney organoids. Immunofluorescence assessed PODOCIN expression and subcellular localization. Podocytes were transcriptionally profiled and PODOCIN-NEPHRIN interaction interrogated. Results: All variant lines revealed reduced levels of PODOCIN protein in the absence of reduced transcription. Although wild-type PODOCIN localized to the membrane, distinct variant proteins displayed unique patterns of subcellular protein trafficking, some unreported. P118L and R138Q were preferentially retained in the endoplasmic reticulum (ER); R168H and R291W accumulated in the Golgi. Podocyte profiling demonstrated minimal disease-associated transcriptional change. All variants displayed podocyte-specific apoptosis, which was not linked to ER stress. NEPHRIN-PODOCIN colocalization elucidated the variant-specific effect on NEPHRIN association and hence NEPHRIN trafficking. Conclusions: Specific variants of endogenous NPHS2 result in distinct subcellular PODOCIN localization within organoid podocytes. Understanding the effect of each variant on protein levels and localization and the effect on NEPHRIN provides additional insight into the pathobiology of NPHS2 variants. Podcast: This article contains a podcast at https://dts.podtrac.com/redirect.mp3/www.asn-online.org/media/podcast/JASN/2023_01_05_JASN2022060707.mp3